Penetrating Posterior Urethral Injuries: Case Report and Management Strategies - Seyed Sajjad Tabei; Brandon Lippold; Wesley Baas; Gregory Murphy (Case Reports in Urology)
Penetrating posterior urethral trauma from gunshot wounds (GSW) is rare and requires prompt treatment to minimize complications. Data regarding the management of such cases is scarce in the literature and poorly addressed in the guidelines. Different management approaches exist, including urinary diversion with immediate versus delayed urethroplasty/fistula repair. We present our case series to add to our experience to the literature. Three patients aged 18–44 presented with ballistic posterior urethra injuries from GSW. Initial management involved urethral catheter placement, with one patient requiring operative placement of urethral and suprapubic catheters (SPTs). Complications included recurrent membranous stricture, urinary retention, rectourethral fistula, and erectile dysfunction (ED). Posterior urethral injuries from GSW are complex as they can be either isolated or affect adjacent organs. Bladder, ureteral, and urethral injuries must be ruled out. Unlike bladder neck injuries, immediate urethroplasty/fistula repair would be very challenging and not advised for standard prostatic or membranous injuries. Urethral catheter or suprapubic tube is recommended and can result in fistula closure and urethral patency. It is critical to maintain close follow-up with the patient due to the possibility of stricture recurrence. Urethroplasty in a delayed fashion can be very successful.